Central Pontine Myelinolysis in Association with Correction of Hypokalemia with Asymptomatic Case of Gastroesophageal Reflux Disease - Paudel, Subash; Chandra, Avinash; Pahwa, Bhavya; Shrestha, Janam; Shrestha, Dinuj; Chandra, Ayush (Annapurna Journal of Health Sciences, 2023)
This case report has described the patient having the central pontine myelinolysis (CPM) associated with hypokalemia correction with asymptomatic history of gastroesophageal reflux disease (GERD). It was suspected that due to GERD and vomiting there might be loss of electrolytes resulting to hypokalemia. The hypokalemia was corrected and patient was discharged from the tertiary neurological center in Nepal.Central Pontine Myelinolysis in Association with Correction of Hypokalemia with Asymptomatic Case of Gastroesophageal Reflux Disease.